Prototype of Water Tank Level Control for Drinking Water of Santri at Al-Amanah Modern Islamic Boarding School Based on IoT with Solar Power: Prototype Kontrol Level Tandon Air minum Santri di Pesantren Modern Al-Amanah Berbasis IoT Dengan Tenaga Matahari - Abdillah, Abdillah; Solikin, Akhmad (Muhammadiyah University, Sidoarjo, 2025)
Water is a vital resource for life on earth and a primary human need. This research is motivated by water management issues within the Al-Amanah Modern Islamic Boarding School, where the tank filling process is still carried out manually, often resulting in waste and the absence of water level indicators. To address this issue, an Internet of Things (IoT)-based water level control system was designed. This system utilizes an ultrasonic sensor to measure the water level, a NodeMCU ESP8266 as the main controller, and the Blynk application to monitor and control the system via a smartphone. A relay is used to automatically turn the water pump on and off. Data from the sensor is processed by a microcontroller, sent to the Blynk server, and displayed in real time in the application. Test results show that the system is able to monitor and regulate water filling more efficiently, although overall performance still has room for improvement.